Good Mob, Bad Mob: Violence and Community in The Cattle Queen of Montana (1894) - Rose, David (Current Objectives of Postgraduate American Studies, 2012)
Focusing on the genre of the Western pioneer narrative, notably Mrs. Nat. Collins’s The Cattle Queen of Montana“ (1894), the article will discuss literary representations of violence and community in the context of the accelerating westward movement on the North American continent around the mid-nineteenth century. Drawing on the theories of Georges Sorel and Richard Slotkin, the article emphasizes the productive dimensions of violence and argues for an increased recognition of the multiple intersections that connect violent acts to processes of communal bonding. The settling of the American continent was an intrinsically violent endeavor, and consequently, it will be argued, violence became a fundamental factor in shaping the modes of social interaction and communal cohesion in the ‘new’ nation. The literary accounts of Western pioneer narratives in general provide fascinating insights into these intricate processes and contribute to an enhanced understanding of the role of violence in the settling of the West. Collins’s narrative, while maintaining a clear-cut division between the ‘acceptable’ violence of the settlers as opposed to the ‘unacceptable’ violence of the natives, relates the inherent brutality of frontier conditions with unflinching bluntness and at the same time reflects on the repercussions this violence has on emerging structures of community. By providing a reading of this narrative as well as of some of the illustrations that accompany it, the article will highlight the continuities between violence and community in the mid- nineteenth century United States and the role Western pioneer narratives played in developing these continuities.